Smartphone-based device for point-of-care diagnostics of pulmonary inflammation using convolutional neural networks (CNNs) - Mohammadreza Ghaderinia; Hamed Abadijoo; Ashkan Mahdavian; Ebrahim Kousha; Reyhaneh Shakibi; S. Mohammad-Reza Taheri; Hossein Simaee; Ali Khatibi; Ali Akbar Moosavi-Movahedi; Mohammad Ali Khayamian (Scientific Reports, 2024)
Abstract In pulmonary inflammation diseases, like COVID-19, lung involvement and inflammation determine the treatment regime. Respiratory inflammation is typically arisen due to the cytokine storm and the leakage of the vessels for immune cells recruitment. Currently, such a situation is detected by the clinical judgment of a specialist or precisely by a chest CT scan. However, the lack of accessibility to the CT machines in many poor medical centers as well as its expensive service, demands more accessible methods for fast and cheap detection of lung inflammation. Here, we have introduced a novel method for tracing the inflammation and lung involvement in patients with pulmonary inflammation, such as COVID-19, by a simple electrolyte detection in their sputum samples. The presence of the electrolyte in the sputum sample results in the fern-like structures after air-drying. These fern patterns are different in the CT positive and negative cases that are detected by an AI application on a smartphone and using a low-cost and portable mini-microscope. Evaluating 160 patient-derived sputum sample images, this method demonstrated an interesting accuracy of 95%, as confirmed by CT-scan results. This finding suggests that the method has the potential to serve as a promising and reliable approach for recognizing lung inflammatory diseases, such as COVID-19.